Weighted Estimates of a Class of Integral Operators with Three Parameters. (30th April 2016) - Oinarov, Ryskul; Kalybay, Aigerim
Abstract : We characterize the validity of a Hardy-type inequality with a kernel and three parameters 1 < p, q, r < ∞ under some conditions on three weight functions u, v, and w .